Impact of Surgical Approach on Surgical Resection Quality in Mid- and Low Rectal Cancer, A Bayesian Network Meta-Analysis - Wang, Xiaojie; Zheng, Zhifang; Yu, Qian; Ghareeb, Waleed M.; Lu, Xingrong; Huang, Ying; Huang, Shenghui; Lin, Shuangming; Chi, Pan (Frontiers in Oncology, 2021)
AIM: To evaluate the evidence concerning the quality of surgical resection in laparoscopic (LapTME), robotic (RobTME) and transanal (TaTME) total mesorectal excision for mid-/low rectal cancer. METHODS: A systematic literature search of the PubMed, EMBASE and Cochrane Central Register of Controlled Trials databases was performed. A Bayesian network meta-analysis was utilized to compare surgical resection involved in these 3 surgical techniques by using ADDIS software. Rates of positive circumferential resection margins (CRMs) were the primary endpoint. RESULTS: A total of 34 articles, 2 randomized clinical trials (RCTs) and 32 non-RCTs, were included in this meta-analysis. Pooled data showed CRM positivity in 114 of 1763 LapTME procedures (6.5%), 54 of 1051 RobTME procedures (5.1%) and 60 of 1276 TaTME procedures (4.7%). There was no statistically significant difference among these 3 surgical approaches in terms of CRM involvement rates and all other surgical resection quality outcomes. The incomplete mesorectal excision rates were 9.6% (69/720) in the LapTME group, 1.9% (11/584) in the RobTME group and 5.6% (45/797) in the TaTME group. Pooled network analysis observed a higher but not statistically significant risk of incomplete mesorectum when comparing both LapTME with RobTME (OR = 1.99; 95% CI = 0.48-11.17) and LapTME with TaTME (OR = 1.90; 95% CI = 0.99-5.25). By comparison, RobTME was most likely to be ranked the best or second best in terms of CRM involvement, complete mesorectal excision, rate of distal resection margin (DRM) involvement and length of DRMs. In addition, RobTME achieved a greater mean tumor distance to the CRM than TaTME. It is worth noting that TaTME was most likely to be ranked the worst in terms of CRM involvement for intersphincteric resection of low rectal cancer. CONCLUSION: Overall, RobTME was most likely to be ranked the best in terms of the quality of surgical resection for the treatment of mid-/low rectal cancer. TaTME should be performed with caution in the treatment of low rectal cancer.